eCM 2014
DOI: 10.22203/ecm.v027a15
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of animal models for Staphylococcus aureus osteomyelitis

Abstract: Staphylococcus aureus (S. aureus) osteomyelitis is a significant complication for orthopaedic patients undergoing surgery, particularly with fracture fixation and arthroplasty. Given the difficulty in studying S. aureus infections in human subjects, animal models serve an integral role in exploring the pathogenesis of osteomyelitis, and aid in determining the efficacy of prophylactic and therapeutic treatments. Animal models should mimic the clinical scenarios seen in patients as closely as possible to permit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
106
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 131 publications
(107 reference statements)
2
106
0
1
Order By: Relevance
“…In a recent review on S. aureus osteomyelitis and animal models published, the authors clearly showed the limitations of various animal models concerning the transfer from animal data to the clinical situation (Reizner et al, 2014). We think that choosing a certain material instead of another will not solely solve the problem of implant-associated infections alone but might be one step in reducing the number of infections.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…In a recent review on S. aureus osteomyelitis and animal models published, the authors clearly showed the limitations of various animal models concerning the transfer from animal data to the clinical situation (Reizner et al, 2014). We think that choosing a certain material instead of another will not solely solve the problem of implant-associated infections alone but might be one step in reducing the number of infections.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…The ideal small animal model to study post-infection treatments would utilize a fixation device that maintains stability after infection establishment and can readily accommodate an antibiotic-laden biomaterial spacer in a bone defect following extensive debridement. The limited in vivo evaluation of novel antibiotic spacers and dual-purpose (infection management and bone regeneration) scaffolds may be attributable to the unavailability of such an animal model [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…The range of diseases caused by S. aureus is represented by the diversity of animal model systems currently being studied (28,29). In terms of S. aureus biofilm infection, some models utilize a large infectious inoculum or introduce implants that are precoated with bacteria (30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%